PENGARUH CONTENT MARKETING APLIKASI TIKTOK TERHADAP PEMBENTUKAN BRAND AWARENESS PADA ENGLISH ACADEMY BY RUANGGURU - Gabriella Mayrene; Natalia Junaidi (Jurnal Cakrawala Ilmiah, 2023)
The advancement of time is followed by the advancement of technology and information that ease mankind to share information, as well as to be used in marketing that now has transformed itself into digital marketing. The real form of technological development is the TikTok application that can be used as a digital marketing medium, which content marketing plays a big role in it and related to brand awareness as well. One of business that partake in the advantage of TikTok is English Academy, an online course product owned by Ruangguru that has a TikTok account under the name of @englishacademy_id. Through qualitative method in a form of literature review, this research aims to determine the effect of @englishacademy_id’s content marketing on its brand awareness, the effectiveness of content marketing and brand awareness, and the effectiveness of using TikTok as a medium used by @englishacademy_id. The result of this research are there is a significant effect between content marketing and brand awareness @englishacademy_id on TikTok, content marketing and brand awareness’ effectiveness are relative, and TikTok is the right medium for @englishacademy_id